Becoming a Man: A Duboisian Examination of the Experiences of Black Men Who Have Sex with Men. (25th December 2020) - Barnes, Sandra L
Abstract: W.E.B. Du Bois developed a thesis on the formation of Black manhood that includes key characteristics of this identity and dynamics that can foster or undermine its development. Yet his framework does not directly reference sexual minorities. Is Du Bois' thesis relevant today for Black men who have sex with men (BMSM)? Do they espouse similar traits and experience similar challenges? Are their masculinity tropes nuanced based on racial, gender, and/or sexual identities? Informed by a New Millennium Du Boisian Mode of Inquiry and qualitative analyses, this study considers whether and how key aspects of Du Bois' understanding of the formation of Black manhood are evident among 168 BMSM who reside in the South. Moving beyond a focus on HIV/AIDS for this demographic, the article notes that three themes emerge linked to embracing, essentializing, and extending Du Bois' thesis on Black manhood that illustrate whether and how his views on Black masculinity are apparent and relevant among Black men excluded from his original work.